Developing the racial city: conflict, solidarity and urban traders in late-colonial Mombasa. Issue 3 (3rd July 2017) - Smart, Devin
ABSTRACT: Much of the scholarly literature on race and decolonization in East Africa focuses on how this period created new and exacerbated existing racial tensions, divisions and conflicts between diverse coastal communities that came to increasingly identify or be identified as "African" or "Arab." While this article will examine such a moment in which these two groups came into conflict, it will also consider the possibility and nature of solidarity between Arabs and Africans in late-colonial East Africa. The tension surrounding race and decolonization in Mombasa and the wider Kenyan coast during this period was influenced by Mwambao, a movement advocating for coastal autonomy as independence approached. This article will focus on how the politics of mwambao and race came to shape the ways in which African vendors and hawkers in Mombasa mobilized against a municipal council that had become increasingly authoritarian in its administration of "informal" industries, especially those relating to food, policing them through fines, harassment and the demolition of the structures in which they conducted business. In their struggle to remain in operation in the city, African traders identified the municipal council as an institution that not only repressed them, but also provided structural privileges to Arab traders. Consequently, when the Mombasa African Traders Association (MATA) organized a boycott in 1961 to focus attention on its members' grievances and pressure the municipal council, the association targeted not only city authorities, but also Arab businesses. Part of MATA's concern with Arab traders was they saw them as colluding with Mwambao activists, which they feared meant that Arab advantages in the governing structures of the city would be carried through independence. However, in the face of a wider coastal context that was moving towards conflict and at times even violence between these groups, this article will examine how African and Arab traders in Mombasa were able to alternatively fashion a class-based and anti-colonial solidarity.